PENYELENGGARAAN BIDANG BIMBINGAN BELAJAR OLEH GURU BK TERHADAP PESERTA DIDIK YANG SEKOLAH SAMBIL BEKERJA (Studi Kasus di SMP N 1 Rao Selatan Pasaman Timur) - Nofriyani, Nofriyani; Ibrahim, Indra; Zaini, Ahmad (Bimbingan dan Konseling, 2014)
This research is motivated by a finding that there are learners who study while working at the Junior High School N 1 South Rao. Students who study while working is caused due economic factor that force them the work to fulfill their studying needs. This Research is a descriptive qualitative research. Informants in this study were learners as many as 3 people, and supporting teachers BK informant by 2 people. Data were collected through interviews, observation and documentation. The objective is to describe: (1) stabilization of the attitude and study habits are affective and afficient, (2) strengthening training systems, either independently or in groups. From the analysis of interviews revealed that the students are ready to take the field BK tutoring by teachers against students who school while working,Â but still found obstacles for teachers in the administration of BK tutoring field is limited time to get into the classroom, the teacher is not maximized BK in organizing materials on BK because time has not been scheduled to go to class. Based on the results of the study recommended forheadmaster for provide time to BK teachers in help apply tutoring field.